Acute Effects of Barbell Bouncing and External Cueing on Power Output in Bench Press Throw in Resistance-Trained Men - Saeterbakken, Atle Hole; Loken, Jorund; Solstad, Tom Erik Jorung; Stien, Nicolay; Prieske, Olaf; Scott, Suzanne; Andersen, Vidar (Frontiers in Physiology, 2022)
The aims of this study were to compare power output during a bench press throw (BPT) executed with (BPTbounce) and without (BPT) the barbell bounce technique and examine the effect of cueing different barbell descent velocities on BPT power output in resistance-trained males. Twenty-seven males (age 23.1 ± 2.1 years; body mass 79.4 ± 7.4 kg; height 178.8 ± 5.5 cm; and 4.6 ± 1.9 years of resistance training experience) were recruited and attended one familiarization session and two experimental sessions (EXP 1 and EXP 2). Force-velocity profile during maximal BPT and BPTbounce (randomized order) under different loads (30-60 kg) was established (EXP 1) and the effect of varying external barbell descent velocity cues “slow, medium, and as fast as possible” (i.e., “fast”) on the power output for each technique (BPT and BPTbounce) was examined (EXP 2). Comparing the two BPT techniques (EXP 1), BPTbounce demonstrated 7.9 – 14.1% greater average power (p ≤ 0.001, ES = 0.48 – 0.90), 6.5 – 12.1% greater average velocity (p ≤ 0.001, ES = 0.48 – 0.91), and 11.9 – 31.3% shorter time to peak power (p ≤ 0.001 – 0.05, ES = 0.33 – 0.83) across the loads 30 – 60kg compared to BPT. The cueing condition “fast” (EXP 2) resulted in greater power outcomes for both BPT and BPTbounce compared with the “slow” . No statistically significant differences in any of the power outcomes were observed between “medium” and “slow” cuing conditions for BPT (p = 0.097 – 1.000) whereas BPTbounce demonstrated increased average power- and velocity under the “medium” cuing condition, compared to “slow” (p = 0.006 – 0.007, ES = 0.25 – 0.28). No statistically significant differences were observed in barbell throw height comparing BPT and BPTbounce under each cuing condition (p = 0.225 – 1.000). Overall, results indicate that both bouncing the barbell and emphasizing barbell descent velocity be considered to improve upper body power athlete and non-athlete resistance training programmes.